The relationship between self-compassion, coping style, sleep quality, and depression among college students - Wang, Yiwen; Fu, Tiantian; Wang, Jun; Chen, Shufeng; Sun, Guoxiao (Frontiers in Psychology, 2024)
The prevalence of sleep quality problems and depression in the college student population has attracted widespread attention. However, the factors influencing this are still unclear. The objective of this study was to investigate the associations between self-compassion (S-C), sleep quality (SQ), and depression (DEP) among college students and examine the mediating effects of coping style (CS) between the variables.Methods: A total of 1038 Chinese university students were recruited for the study. The study used the Self-Compassion Scale (SCS), Simplified Coping Style Questionnaire (SCSQ), Depression Anxiety Stress Scale 21 (DASS-21), and Pittsburgh Sleep Quality Index (PSQI) to conduct the survey.The self-compassion and coping style showed significant negative correlations with sleep quality and depression. Coping style partially mediated the relationship between self-compassion and sleep quality. The coping style also fully mediated the relationship between self-compassion and depression.This study reveals the associations between self-compassion and sleep quality and depression, and the mediating role of coping style among college students.This study provides valuable insights for improving sleep quality and alleviating depression problems among college students. It emphasizes the importance of selfcompassion and positive coping style.